Legal Protection for Unilateral Layoffs of Additional Workers at Teluk Nibung Port Following the Enactment of Government Regulation No. 35 of 2021 from a Maqashid Sharia Perspective - Silvia Arma; Muhammad Ramadhan (LP2M IAIN Palopo, 2026)
Additional Workers (TKT) at Teluk Nibung Port in Tanjung Balai City are vulnerable subjects in industrial relations in Indonesia. This study aims to analyze the legal protection for TKT who experienced unilateral termination of employment (PHK) by the port in 2023, after working since 1996, without compensation. Legally, the status of workers who worked for years with verbal agreements and the continuous nature of the work indicates an indefinite-term employment relationship (PKWTT), regardless of the formal designation